Media Edukasi Kerajaan Besar Hindu, Budha, Islam Di Indonesia Berbasis Android (Information Technology and Telematics, 2014)
Abstraction Technological developments in Indonesia for rapid information system, it is evident the moment almost all the educational institutions have been many who use information systems to facilitate the learning process there. One of the technologies used for the delivery of this information is the medium of learning using technology. This study aims at designing media recognition and learning about the great kingdom of Hindu, Buddhist, Islam in Indonesia, as well as the media can make learning and recognition applications that can provide information and learning for its users and authors. This application uses the system development life cycle methodology that has five stages: perancanaan, analysis, design, implementation and evaluation. This application is built using the Java programming language. In this application pembuataan using Eclipse software, which uses java language. Designing media recognition and learning aims to provide information empire Hindu, Buddhist, Islamic and android-based recall the history of the great empire which had triumphed in his time. Diamping it is expected to improve the quality of education on the history, especially the history of the major kingdoms in Indonesia. Keywords : system development life cycle, java, Eclipse